2022
DOI: 10.3390/languages8010007
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Teaching in Refugee Children within the Context of the Greek Formal Education

Abstract: The aim of the present study is to investigate vocabulary teaching in children with refugee backgrounds. The effectiveness of three vocabulary interventions—flashcards, pantomime, and use of contextual cues—is examined within the context of formal primary education in Greece. The improvement of the children’s vocabulary is also assessed in association with factors related to the students’ background as well as factors related to the words taught. Thirty-three pupils from the second to the sixth primary school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Online classes disrupted traditional curriculum delivery. As well, students were restricted from taking part in regular school activities (e.g., arts programs), which generally help second-language vocabulary learning (Olioumtsevits et al, 2022); they also lost their familiarization with nonverbal practices common in formal school settings, which also tend to promote rapid language acquisition (Simopoulos & Magos, 2020). Research has found that the in-person formal learning experiences of refugee children in Greece were among their happiest moments since arriving in the country.…”
Section: Harmful and Extended Lockdownsmentioning
confidence: 99%
“…Online classes disrupted traditional curriculum delivery. As well, students were restricted from taking part in regular school activities (e.g., arts programs), which generally help second-language vocabulary learning (Olioumtsevits et al, 2022); they also lost their familiarization with nonverbal practices common in formal school settings, which also tend to promote rapid language acquisition (Simopoulos & Magos, 2020). Research has found that the in-person formal learning experiences of refugee children in Greece were among their happiest moments since arriving in the country.…”
Section: Harmful and Extended Lockdownsmentioning
confidence: 99%